The discovery of angiogenic growth factors: the contribution of Italian scientists - Ribatti, Domenico (BioMed Central, 2014)
Angiogenesis is regulated, under both physiological and pathological conditions, by numerous “non-classic” pro-angiogenic factors, including fibroblast growth factor-2 (FGF-2), vascular endothelial growth factor (VEGF), and placental growth factor (PlGF), and “non-classic” pro-angiogenic factors, including granulocyte colony stimulating factor (G-CSF), granulocyte macrophage colony stimulating factor (GM-CSF), and erythropoietin (EPO). In the context of the most important discoveries in this field, this review article summarizes the important role played by the Italian scientists in the course of the last twenty years.